Similar safety and efficacy in previously treated adults with growth hormone deficiency randomized to once‐weekly somapacitan or daily growth hormone - Otsuka, Fumio (Clin Endocrinol (Oxf), 2020)
OBJECTIVE: Somapacitan is a long‐acting, reversible albumin‐binding growth hormone (GH) derivative in development. This study aimed to evaluate the safety and efficacy of once‐weekly somapacitan versus daily GH over 52 weeks in Japanese patients with adult growth hormone deficiency (AGHD). DESIGN: Phase 3, multicentre, randomized, parallel‐group, open‐label, active‐controlled trial (NCT03075644). PATIENTS: Previously GH‐treated Japanese patients with AGHD were randomized 3:1 to somapacitan (n = 46) or daily GH (n = 16) for 20 weeks’ dose titration and 32 weeks’ fixed‐dose treatment. MEASUREMENTS: Primary endpoint was the incidence of adverse events (AEs). Secondary endpoints included change from baseline to week 52 in visceral, subcutaneous and total adipose tissue (VAT, SAT and TAT). RESULTS: Mean (SD) prescribed doses after titration were 1.780 (1.058) mg/week for somapacitan and 0.197 (0.083) mg/day for daily GH. Rate of AEs per 100 patient‐years was similar between arms (somapacitan, 312.7; daily GH, 309.8). Four AEs in the somapacitan arm were serious; none were considered treatment‐related. Mean insulin‐like growth factor‐I standard deviation score (IGF‐I SDS) was maintained from baseline in both arms. No significant differences were observed between arms for change from baseline to week 52 in VAT, SAT or TAT (estimated difference, somapacitan – daily GH [95% CI]: −1.74 [−18.13; 14.66], −11.53 [−35.54; 12.48] and − 12.85 [−47.31; 21.62] cm(2), respectively). CONCLUSIONS: Treatment in both groups was well tolerated, with no unexpected safety findings. Impact on adipose tissue was similar to somapacitan and daily GH in patients with AGHD. A short visual summary of our work is available at https://bit.ly/3946YNF.